Genesis and Origin of the Esoteric Culture in White Shamanism: A Historical–Cultural Analysis. (October 2015) - Relic, Ratka
In the article, a scientific explanation is given about the origin of the white shamanism according to Buryatia and Mongolian shamanic traditions and the very shamanic esotericism of Tengerism, precisely its connection with Indo-Iranian cultural tradition and the tradition of the Indus Valley civilization, with D.N. Dugarov's explanation based on his historical and archaeological research.